Intracellular activity of antimicrobial compounds used for Staphylococcus aureus nasal decolonization. (16th August 2018) - Rigaill, J; Morgene, M F; Gavid, M; Lelonge, Y; He, Z; Carricajo, A; Grattard, F; Pozzetto, B; Berthelot, P; Botelho-Nevers, E; Verhoeven, P O
Abstract: Background: Staphylococcus aureus is able to invade mammalian cells during infection and was recently observed inside nasal mucosa of healthy carriers. Objectives: To determine the intracellular activity of antimicrobial compounds used for decolonization procedures using a cell model mimicking S. aureus nasal epithelium invasion. Patients and methods: HaCaT cells and human nasal epithelial cells (HNECs) recovered from nasal swabs of S. aureus carriers were visualized by confocal laser scanning microscopy to detect intracellular S. aureus cells. An HaCaT cell model, mimicking S. aureus internalization observed ex vivo in HNECs, was used to assess the intracellular activity against S. aureus of 21 antimicrobial compounds used for nasal decolonization, including mupirocin and chlorhexidine. Results: HaCaT cells and HNECs were found to internalize S. aureus with the same focal pattern. Most antimicrobial compounds tested on HaCaT cells were shown to have weak activity against intracellular S. aureus . Some systemic antimicrobials, including fusidic acid, clindamycin, linezolid, minocycline, ciprofloxacin, moxifloxacin, rifampicin and levofloxacin, reduced S. aureus intracellular loads by 0.43–1.66 log cfu/10 6 cells compared with the control ( P < 0.001). By contrast, mupirocin and chlorhexidine reduced the S. aureus intracellular load by 0.19 and 0.23 log cfu/10 6 cells, respectively. Conclusions: These data indicate that most of the antimicrobial compounds used for nasal decolonization, including mupirocin and chlorhexidine, exhibit weak activity against intracellular S. aureus using the HaCaT cell model. This work emphasizes the need to better understand the role of the S. aureus intracellular reservoir during nasal colonization in order to improve decolonization procedures.